METHOD OF PREORTHODONTICAL TREATMENT OF CHILDREN LIVING IN DIFFERENT ENVIRONMENTAL CONDITIONS - Rozhko-Hunchak, O.M.; Nespryadko, V.P. (World of Medicine and Biology, 2012)
140 children 7 years old, that living in ecologically unfavorable conditions, with pathology of bite in the saggital plane were examined and treated. We formed three groups of children: group 1 - 60 children treated with the improved method (splints-caps); 2 group - 60 children treated generally known methods; group 3 – control, 20 children. A study of preorthodontical treatment by improved method using individual splints-cap proves the effectiveness of the method is expressed in preventing the development and prevention of deformities in children living in ecologically unfavorable conditions.
Keywords: children; preorthodontical treatment; dento-alveolar deformations; articulator; splint-cap